2008
DOI: 10.1111/j.1471-4159.2008.05353.x
|View full text |Cite|
|
Sign up to set email alerts
|

THIS ARTICLE HAS BEEN RETRACTED: Toll‐like receptor 3 contributes to spinal glial activation and tactile allodynia after nerve injury

Abstract: Toll-like receptors (TLRs) play an essential role in innate immune responses and in the initiation of adaptive immune responses. Microglia, the resident innate immune cells in the CNS, express TLRs. In this study, we show that TLR3 is crucial for spinal cord glial activation and tactile allodynia after peripheral nerve injury. Intrathecal administration of TLR3 antisense oligodeoxynucleotide suppressed nerve injury-induced tactile allodynia, and decreased the phosphorylation of p38 mitogen-activated protein ki… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
65
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 70 publications
(69 citation statements)
references
References 46 publications
4
65
0
Order By: Relevance
“…These data indicate that TLR3 is critical for the development of neuropathic pain [83]. Since TLR3 binds mRNA released from necrotic cells it has been suggested that this may be the mechanism responsible for the TLR3 role in neuropathic pain [79].…”
mentioning
confidence: 83%
See 3 more Smart Citations
“…These data indicate that TLR3 is critical for the development of neuropathic pain [83]. Since TLR3 binds mRNA released from necrotic cells it has been suggested that this may be the mechanism responsible for the TLR3 role in neuropathic pain [79].…”
mentioning
confidence: 83%
“…This type of pain in not protective and is itself regarded as a pathological condition [82]. In contrast to inflammatory pain, treatments for neuropathic pain is lacking, and therefore is a requirement to understand its molecular pathogenesis [83]. It is now thought that the basis of neuropathic pain requires immune activation in the CNS, where the production of chemokines and cytokines triggers the expression of pain mediators such as glutamate and NO [80,[84][85][86].…”
Section: Of 62mentioning
confidence: 99%
See 2 more Smart Citations
“…Mice lacking either toll‐like receptor 2, 3 or 4 show impaired microglial activation in the dorsal horn after PNI42, 43, 44.…”
Section: Microglia In the Spinal Cord In Pni And Diabetic Animalsmentioning
confidence: 99%